(untitled) (Fiep Bulletin - online, 2013)
Noting some lessons of Physical Education school realizes that there is great distance between theory and practice as in theory one should provide a lesson for all of Physical Education, where boys and girls participating together, but what is present in class Fitness is for boys and girls here to get there. Thus, this research looks the contributions of the dance hall of gaúcha for relations between genres from lessons of Physical Education applied to elementary school students from the Indiana State College in the municipality of San Miguel do Iguacu - PR. This study was conducted by searching pre-trial, in the municipality of San Miguel do Iguacu, in dependencies of the State College Castelo Branco, in the classes of Physical Education of a class of 7th grade of the morning round with 34 students. It was conducted through observations before and after school practices of dancing and conducting interviews with teachers of the class, after the application of lessons. 10 lessons were applied practice of Physical Education, between the months of March to May, involving the contents dance, and approximately 4 lessons per month. The instruments that were used for data collection are: semi structured with no fixed itinerary; sheets observation; recorder, photos, test pilot. The analysis of qualitative data was by way of content analysis by categorizing the answers. From the analysis of the data, we can conclude that the dance hall of gaúcha can contribute to a better relationship between genders in school by stimulating and facilitating the practice of dancing in the south and rescuing cultural values.